Co-catalyzed mild and chemoselective reduction of phenyl esters with NaBH(4): a practical synthesis of (R)-tolterodine - Jagdale, Arun R.; Sudalai, Arumugam (Tetrahedron Letters, 2008)
CoCl(2) catalyzes effectively the chemoselective reduction of phenyl carboxylic esters to the corresponding saturated alcohols in high yields using NaBH(4) at ambient conditions. By employing this methodology, the synthesis of (R)-tolterodine, a muscarinic receptor antagonist, has been achieved in high yield and optical purity. (C) 2008 Elsevier Ltd. All rights reserved.

Cu(OTf)(2) catalyzed Biginelli type condensation of aldehydes, beta-keto esters and carbamates: synthesis of 3,4-dihydro[1,3]oxazin-2-ones - Jagdale, Arun R.; Paraskar, Abhimanyu S.; Sudalai, Arumugam (Indian Journal of Chemistry Section B-Organic Chemistry including Medicinal Chemistry, 2008)
Cu(OTf)(2) catalyzes effectively a new multicomponent reaction comprising aldehydes, beta-ketoester and methy carbamate in acetonitrile to afford substituted 3,4-dihydro[1,3]oxazin-2-ones in 60-82% yields. These compounds have been found to show inhibition activity against HL-60 cancer cell.
Keywords: aldehydes; Catalysts; Copper; Multicomponent reaction

Asymmetric synthesis of tetrahydroquinolin-3-ols via CoCl2-catalyzed reductive cyclization of nitro cyclic sulfites with NaBH4 - Jagdale, Arun R.; Reddy, R. Santhosh; Sudalai, Arumugam (Organic Letters, 2009)
A new method for the construction of chiral 3-substituted tetrahydroquinoline derivatives based on asymmetric dihydroxylation and CoCl2-catalyzed reductive, cyclization of nitro cyclic sulfites with NaBH4 has been described with high optical purities. This method has been successfully applied in the formal synthesis of PNU 95666E and anachelin H chromophore.

Cobalt(II) chloride hexahydrate-diisopropylamine catalyzed mild and chemoselective reduction of carboxylic esters with sodium borohydride - Jagdale, Arun R.; Paraskar, Abhimanyu S.; Sudalai, Arumugam (Synthesis-Stuttgart, 2009)
The cobalt-catalyzed reduction of unsaturated alpha-cyano carboxylic esters using sodium borohydride (NaBH(4)) leads to the corresponding saturated cyano alcohols in high yields. In particular, the new catalytic system cobalt(II) chloride-diisopropylamine in combination with NaBH(4) showed excellent activity in the chemoselective reduction of a variety of carboxylic esters to their corresponding alcohols in good to excellent yields under mild conditions.
Keywords: Alcohols; amines; catalysis; Esters; reductions

Concise enantioselective synthesis of 1-[(S)-3-(dimethylamino)-3,4 dihydro-6,7-dimethoxyquinolin-1(2H)-yl]propan-1-one, (S)-903 - Jagdale, Arun R.; Reddy, R. Santhosh; Sudalai, Arurnugam (Tetrahedron-Asymmetry, 2009)
A concise enantioselective synthesis of (S)-903, an inotropic agent, is described in nine linear steps and 95% ee based on asymmetric dihydroxylation of cinnamate ester and Co-catalyzed Multifunctional reduction of several functional groups leading to the construction of core tetrahydroquinolin-3-ol, as the key steps. (C) 2009 Elsevier Ltd. All rights reserved.

Cu(OTf)(2)-catalyzed alpha-halogenation of ketones with 1,3-dichloro-5,5 `-dimethylhydantoin and N-bromosuccinimide - Jagdale, Arun R.; Chouthaiwale, Pandurang V.; Sudalai, Arumugam (Indian Journal of Chemistry Section B-Organic Chemistry including Medicinal Chemistry, 2009)
Copper(II) triflate catalyses efficiently the alpha-halogentation of aryl or alkyl ketones with 1,3-dichloro-5,5'-dimethyl-hydantoin and N-bromosaccinimde to give the corresponding alpha,alpha-dichloroketones and alpha-bromoketones in high yield with excellent product selectivity.
Keywords: Bromination; Catalyst; chlorination; copper (II); Ketone; Lewis acid